Evaluation and comparison of drying models in open sun drying and photovoltaic and LPG burner assisted hybrid solar drying system - Tubagus Rayyan Fitra Sinuhaji; Suherman Suherman; Hadiyanto Hadiyanto; Ardi Ardan; Sulistia Rahmawati (Case Studies in Chemical and Environmental Engineering)
This study evaluates the drying performance of open sun drying (OSD) and photovoltaic and LPG burner assisted hybrid solar drying system (HSD) systems for cocoa beans. OSD, a traditional and cost-effective method, faces limitations such as extended drying times, susceptibility to environmental contamination, and inconsistent quality. In contrast, HSD integrates solar energy with auxiliary heat sources, providing controlled drying conditions and improved efficiency. The research involved experimental comparisons between the two methods, using cocoa beans as the primary material. Measurements included temperature, relative humidity, drying duration, and energy utilization. Data were analyzed with thin-layer drying models, with the Midili model being the most accurate (R2 > 0.98). Drying trials were conducted at 40 °C, 45 °C, and 50 °C, with the target moisture content set at 7–8%. Results showed that HSD achieved superior performance, reducing drying times to 3–4 hours compared to 23 hours for OSD. HSD also demonstrated higher exergy efficiencies (94.6614 %) and lower exergy loss (0.0062 kJ/s). Furthermore, the controlled environment minimized contamination risks and preserved the quality of the cocoa beans. This study concludes that HSD significantly enhances drying efficiency, product quality, and sustainability compared to OSD. These findings suggest that hybrid drying technologies hold great potential for modernizing agricultural drying practices while addressing energy and environmental challenges.